Transient quasi-3D magneto-thermal analytical solution in PM induction heating device. Issue 5 (23rd May 2020) - Abdi, Ammar; Ouazir, Youcef; Barakat, Georges; Amara, Yacine
Abstract : Purpose: This paper aims to develop a new quasi-three dimensional (3D) analytical model devoted to the study of nonlinear transient magneto-thermal coupled problems in permanent magnet (PM) transverse flux induction heating device (TFIHD). Design/methodology/approach: The presented work is based on analytical development of strongly coupled problem, including electromagnetic and thermal boundary problems. The electromagnetic problem is first solved by using the separation variables method to evaluate the induced currents in the nonmagnetic plate and the resulting power density loss distribution. The plate temperature profile is then obtained thanks to strong involvement of this magnetic model in a new analytical thermal model combining the separation of variables method and the Green's functions transient regime analysis method. The coupled model is then used in a simulation procedure of the magneto-thermal process allowing taking into account the workpiece electrothermal nonlinear properties. The developed coupled model is validated by computing the performances of the studied PM TFIHD and comparing them to those obtained by finite element simulations. Finding: An efficient transient quasi-3D magneto-thermal analytical model is developed allowing rapid analysis of PM induction heating for core heating of parallelepiped parts. The developed model also allows fast and accurate simulations of nonlinear and transient three dimensional (3D) magneto-thermal phenomena for planar induction heaters. Research limitations implications: The developed quasi-3D magneto-thermal analytical model is limited to design induction heating devices of planar structure with PM inductors. Originality/value: A new transient quasi-3D magneto-thermal analytical model accounts for non-linearity and edge effect and helps to fast study and fast design of linear permanent magnet induction heating device.